Investigating Students’ Reading Habit in Learning English at Islamic Boarding Senior High School Babussalam Pekanbaru - Suci Anggraini; Bukhori Bukhori (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Reading habit refers to the behavior which expresses the likeness of reading of individual types of reading and tastes of reading (Sangkaeo 1999) cited in Chettri and Rout (2011). However, the students at the Eleventh Grade Students of Islamic Boarding Senior High School in Pekanbaru were not always go to the library to read books or may borrow books, but sometimes they go. This research wanted to describe the students’ reading habit. The design of this research is descriptive quantitative research. The population of the research was the eleventh grade of Islamic Boarding Senior High School in Pekanbaru and the sample were 26 students. The number of sample is selected by using simple random sampling technique. To get the data, the writer employed a close-ended questionnaire. The result showed that majority students at the eleventh grade of Islamic Boarding Senior High School in Pekanbaru had a good reading habit. Meanwhile, some of them showed that they have fair reading habit and of them don’t have good reading habit it is categorized as poor. It can be concluded that the students at the eleventh grade of Islamic Boarding Senior High School in Pekanbaru had various reading habit.